MO850: Casirivimab/Imdevimab in Vaccinated Chronic Haemodialyzed Patients With Acute Mild Covid-19: Safety And Efficiency. (3rd May 2022) - Monge, Matthieu; Henriquez, Soledad; Humbert, Caroline; Guiard, Elsa; Allouache, Mahmoud; Yhuel, Jean-Marc; Lavollay, Marie; Richaud, Clemence; Gohari, Afsaneh
Abstract: BACKGROUND AND AIMS: Casirivimab/imdevimab (C/I) is a combination of two neutralizing human monoclonal antibodies against the SARS-CoV-2. It has been approved for primary prophylaxis or acute SARS-CoV-2 infection in patients with a poor vaccine response. Chronic haemodialyzed (CHD) patients are a high-risk population for both severe COVID-19 and impaired vaccine response. We herein report the safety and efficiency of C/I in CHD patients with acute mild COVID-19. METHOD: In a single-centre haemodialysis facility, all 56 CHD patients received 3 injections of anti-COVID-19 mRNA BNT162b2 vaccine, with anti-S protein antibodies response assessed 7 months after the last injection. During follow-up, patients who presented an acute mild SARS-CoV-2 infection without the need for oxygen therapy and a poor vaccine response received within 5 days after diagnosis 600mg/600mg of C/I. The combination of monoclonal antibodies was infused only once after the end of the dialysis session during 20 min. Patients were kept under surveillance during 1 h before discharge. Efficiency was assessed by RT-PCR 7 days after C/I infusion and clinical evaluation. RESULTS: Six CHD patients had an acute COVID-19 without oxygen therapy requirement and four had a vaccine response < 264 BAU/mL. Among them three had the Delta variant (L452R mutation), and received C/I. Two of them had the opportunity to have a fourth vaccine injection, but got infected within 2 weeks after the boost. Clinical data are summarized in Table 1 . No patient presented any adverse effect within the time in the dialysis facility. During follow-up, all patients remained asymptomatic and all control RT-PCR performed 7 days after infusion were negative. CONCLUSION: 600 mg/600 mg of C/I is a safe and efficient treatment for CHD patients with a poor vaccine humoral response presenting mild acute Delta variant COVID-19 without oxygen requirement.